Microstructural and optical properties of ZrON/Si thin films - Atuchin, V.V.; Kruchinin, V.N.; Wong, Y.H.; Cheong, K.Y. (Elsevier, 2013)
ZrON/Si(100) layer structure formation has been produced by oxidation/nitridation of sputtered Zr metal in N2O/Ar ambient at 500–900 °C. Micromorphology and structural properties of the films have been evaluated by scanning electron microscopy, atomic force microscopy, and reflection high-energy electron diffraction. Dispersive optical properties of the ZrON/Si reflection system have been studied with spectroscopic ellipsometry. A drastic increase of SiO2-based interface layer thickness has been found at 700–900 °C.